PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN PERSON-JOB FIT TERHADAP WORK ENGAGEMENT INDUSTRI KREATIF YOGYAKARTA - Agustini Dyah Respati (Jurnal Riset Manajemen dan Bisnis, 2024)
ABSTRACT This study aimed to investigate the impact of transformational leadership and person-job fit on the work engagement of members of the Pokoke Blangkon Cooperative, which operates in Yogyakarta’s creative industry, primarily offering photography services with traditional Yogyakarta attire. The members of Pokoke Blangkon Cooperative also work as photographers, wardrobe stylists, makeup artists, as well as works in administration and finance. Data for the study were collected from 44 respondents through questionnaires distributed directly to the respondents at the Pokoke Blangkon Cooperative office in Malioboro, Yogyakarta. The data were subsequently analyzed using multiple linear regression through SPSS 25 software. The results indicate that transformational leadership, which has been implemented by the leader of Pokoke Blangkon Cooperative, does not have a significant impact on the work engagement of the cooperative members. On the other hand, person-job fit variable was found to have a significant effect on the work engagement of the cooperative members. This study explores the influence of transformational leadership from the cooperative's chairman, who is both the founder of the cooperative and a respected community figure in the Sosromenduran area of Yogyakarta, as well as the person-job fit, on the work engagement of members in performing their duties within the cooperative. Keywords: transformational leadership, person-job fit, work engagement, creative industry. ABSTRAK Penelitian ini bertujuan untuk menguji pengaruh variabel kepemimpinan transformasional dan person-jon fit terhadap work engagement anggota Koperasi Pokoke Blangkon yang bergerak di bidang industri kreatif di Kota Yogyakarta. Bidang usaha utamanya adalah jasa fotografi dengan busana adat Yogyakarta. Anggota Koperasi Pokoke Blangkon ini juga menjadi karyawan sebagai fotografer, penata busana, perias dan administrasi serta keuangan. Data penelitian dikumpulkan dari 44 responden melalui kuesioner yang diberikan secara langsung kepada responden di kantor Koperasi Pokoke Blangkon di Malioboro Yogyakarta. Selanjutnya data penelitian dianalisis dengan regresi linear berganda melalui program SPSS 25. Hasil penelitian menunjukkan bahwa variabel kepemimpinan transformasional yang sudah diterapkan oleh pemimpin koperasi Pokoke Blangkon tidak berpengaruh terhadap work engagement anggota koperasi. Di sisi lain, variabel person-job fit terbukti berpengaruh signifikan terhadap work engagement anggota koperasi. Penelitian menjajagi pengaruh peran kepemimpinan transformasional dari ketua koperasi sebagai pendiri koperasi dan tokoh masyarakat yang disegani di daerah Sosromenduran Kota Yogyakarta dan person-job fit terhadap work engagement anggota dalam menjalankan tugasnya di koperasi. Kata Kunci: Kepemimpinan transformasional, person-job fit, keterlibatan kerja, industri kreatif